2019
DOI: 10.1177/1120700019884547
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative radiographic evaluation and simulation study for optimal cup placement in high-hip centre total hip arthroplasty

Abstract: Background: Achieving favourable outcomes in high-hip centre reconstruction in hip dysplasia requires the optimal cup height and size, which can provide sufficient bone coverage for stable cup fixation that fits the anteroposterior acetabular rim without increasing the cup height more than necessary. Methods: We retrospectively reviewed 214 patients who underwent primary total hip arthroplasty (THA) and identified 30 hips with Crowe II ( n = 15) or III ( n = 15) developmental dysplasia of the hip (DDH). We mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 21 publications
(28 reference statements)
0
9
0
Order By: Relevance
“…Increasing the contact area between the acetabular cup and the host bone can ensure good initial stability, which is a crucial success factor of hip arthroplasty revision. CC is usually used to evaluate this contact area and in DDH hip replacement ( Yang et al, 2017 ; Liu et al, 2018 ; Mou et al, 2020 ; Takasago et al, 2021 ). Generally, insufficient CC will increase the stress at the bone cup interface, thus increasing the probability of mechanical failure ( Apostu et al, 2018 ; Zuo et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing the contact area between the acetabular cup and the host bone can ensure good initial stability, which is a crucial success factor of hip arthroplasty revision. CC is usually used to evaluate this contact area and in DDH hip replacement ( Yang et al, 2017 ; Liu et al, 2018 ; Mou et al, 2020 ; Takasago et al, 2021 ). Generally, insufficient CC will increase the stress at the bone cup interface, thus increasing the probability of mechanical failure ( Apostu et al, 2018 ; Zuo et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…15 The anteroposterior diameters of the true acetabulum were measured using CT horizontal section, and the cup size was chosen to best accommodate the true acetabulum from a range of 42-66 mm at 2-mm intervals. The 3D cup template was placed based on previous reports, 10,14 at an inclination of 40°and anteversion of 20°in a radiographic definition, as medial as possible, adjacent to the medial wall of the pelvis to obtain maximum bone coverage. The AHC was defined as 15 mm above the inter-teardrop line, 16,17 and cup placement was simulated at the AHC and 10-mm HHC (Figure 1).…”
Section: Computer Simulation Of Cup Placementmentioning
confidence: 99%
“…Although certain simulation studies have reported cup coverage in THA for DDH, most have classified Crowe II and III into one collective group, and few studies have quantitatively evaluated subluxation. [12][13][14] We hypothesized that a boundary exists, indicating sufficient coverage to fix a cementless cup between Crowe II and III. We consider this to be a useful indicator for planning cementless cup placement, especially to evaluate the relationship between the hip's subluxation percentage according to the Crowe classification and cup coverage.…”
mentioning
confidence: 99%
“…It has been accepted that high placement of hip rotation center could simply the operation, increase the coverage rate of acetabular prosthesis, and improve the initial stability of the acetabular cup. However, it is impossible to avoid the improvement of biological stress of the hip joint , the increase of wear rate of the prosthesis, the secondary complications of lower limb length discrepancy, impingement, gluteus medius fatigue, gait changes, dislocation due to the upward migration of the hip rotation center (7)(8)(9). Currently, more and more scholars (6,10,11) proposed anatomical restoration of rotation center in THA for patients with Crowe type II/III DDH, which is beneficial to balance the stress of ligaments and muscles surrounding the hip joint, reduce the wear rate and loosening of the hip prosthesis, whereas it is difficult to restore the hip rotation center and reconstruct the bone defect during the operation.…”
Section: Introductionmentioning
confidence: 99%